The Crisis before "The Crisis": Violence and Urban Neoliberalization in Athens - Dalakoglou, Dimitris (Social justice, 2012)
The article discusses the role of violence in the urban neoliberalization of Athens, Greece following the 2008 global financial crisis, with information on the history of financial regulation and distribution of economic benefits in the country. Topics include the economic and social conditions of the migrant population of Greece, urban redevelopment projects which encouraged the rapid economic growth of the country prior to the financial collapse, and the violent nature of police and military operations targeting undocumented immigrants and foreigners in Greece.